Spinal Cord Stimulation for the Treatment of Chronic Back Pain Patients: 500‐Hz vs. 1000‐Hz Burst Stimulation. Issue 1 (22nd October 2014) - Van Havenbergh, Tony; Vancamp, Tim; Van Looy, Pieter; Vanneste, Sven; De Ridder, Dirk
<x xml:space="preserve">Abstract</x> Objective Spinal cord stimulation is a commonly used, safe, and effective procedure applied for medically intractable failed back surgery syndrome, as well as other neuropathic pain syndromes. Recently, a novel stimulation paradigm called burst stimulation has been developed that is paresthesia‐free and has a more pronounced suppressive effect on neuropathic pain. Materials and Methods Fifteen patients who were being treated with burst spinal cord stimulation for failed back surgery syndrome participated in an open‐label trial to verify whether their pain suppression could be further ameliorated by changing the burst pattern. Burst stimulation with packets of five electrical pulses delivered at 500 Hz with 1000‐μsec pulse width 40 times per second was changed to burst mode delivering five spikes at 1000 Hz with 500‐μsec pulse width 40 times a second. As the amplitudes did not differ between the two groups, the total delivery of current to the spinal cord was not different between the two modes of burst stimulation. Scores on visual analog scales for pain and paresthesia, the Pain Catastrophizing Scale, the Pain Vigilance and Awareness Questionnaire, and the Short Form 36 quality of life measurement were compared between the two modes of burst stimulation. [Correction added on 06 Feb 2015, after first online publication: this paragraph has been revised to signify the comparison of amplitudes between two groups] Results No statistically significant differences were found between the two modes of stimulation. Conclusion The results suggest that increasing the frequency from 500 to 1000 Hz while keeping the pulse width constant does not add any extra benefit in suppressing pain. Further studies should verify whether increasing the frequency above 1000 Hz has a similar lack of effect.